Dünya Savaşı Nasıl Çıkar? İkili Kriz İlişkilerinin (Aktör Çiftleri) Yayılması Üzerinden Dünya Savaşı Olgusunun Uluslararası İlişkilerin Ampirik Bulgularıyla Açıklanması - Öner AKGÜL (Gazi Akademik Bakış)
This study aims to bring an explanation to the world war phenomenon through focusing on how the dyadic crises of states may incline a world war rather than making a systemic level of analysis. To that end, this study based upon the existing findings of empirical international relations theory. The findings of several studies demonstrate that territorial crises, contiguity, protracted conflicts/disputes within dyads, international rivalry issues increases the war proneness of dyads. These war prone dyads may be observed as a bilateral conflict or at the utmost regional war among states. However, these dyads may have a tendency to transform the existing war into a world war as a consequence of contagion. The contagion derived from the alliances, opportunity and willingness of non-belligerents, or behaviors of other major powers involving the crisis.